Implementasi Sistem Pendukung Keputusan dengan Metode Multi-Objective Optimization on The Basis of Ratio Analysis (MOORA) Untuk Pemilihan Karyawan Terbaik - Achmad Sehan; Aprinia Hadayani; Samsoni Samsoni (Journal of Information System Research (JOSH), 2025)
This research aims to develop and implement a Decision Support System (DSS) using the Multi-Objective Optimization on the Basis of Ratio Analysis (MOORA) method to determine the best employee at Hotel Kristal Jakarta. The main problem faced by the hotel is that employee performance assessments are still conducted subjectively, time-consuming, and prone to bias. The MOORA method is chosen because it can handle multi criteria decision making systematically through normalization of the decision matrix and the calculation of the Yi index by combining both benefit and cost criteria. The research begins with the identification of evaluation criteria: knowledge, responsibility, honesty, work productivity, and attendance. Based on interviews with the HRD Director and a literature review. Each criterion is then according to its level of importance. An employee database was built to store the scores for each criterion. The MOORA computation process is implemented using PHP, with a Bootstrap 5-based interface, allowing users (HR admins) to input data, perform automated calculations, and view ranking results in real time. System testing was conducted using data from 15 employees for the May 2025 period. The results show that the system successfully generates employee rankings objectively, the highest Yi value is assigned to the best employee, namely Edy Sarwoko (A6), with a Yi score of 0.218. The implementation of the MOORA-based DSS significantly improves the efficiency of employee evaluation and reduces assessor bias.